Accidents happen to those at the right place and the right time - Taib, Ibrahim Adham (2016)
Reason’s Swiss Cheese Model has been instrumental in explaining how adverse events occur in domains ranging from aviation to healthcare. According to the accident causation model, accidents happen when defences within a system fail to prevent the accident causation process from progressing, and such failures are commonly due to active failures such as mistakes in diagnosis and latent conditions, for example bed shortages and budget cuts. Furthermore, the model suggests that for an accident to occur, the active failures and latent conditions must be interconnected, and the model illustrates this concatenation as an alignment of holes in different layers of Swiss Cheese. That the alignment of holes can occur randomly is incoherent to Islamic teachings because it, among others, excludes God’s role in the accident causation process. The implication of this is that victims of accidents may see themselves as being unlucky, whereas from an Islamic perspective, success and failure in accident prevention or evasion are tests from God the Most Merciful. To some, that accident is from God the Most Merciful seems contradictory. Because of that, this paper shall discuss the Islamic view of accident causation process with reference to Reason’s Swiss Cheese Model and number of ayat from the Quran.